Proposed guidelines for the development of an audiobook collection for the Quezon City Public Library - Aman, Theo Rafael S.; Santos, Yhna Therese P. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2014)
Audiobooks have been available to the public since the early 1960s, but it has yet to gain traction in the Philippines. Audiobooks started out as a way for the visually-impaired to acquire literary entertainment, but ove time sighted people came to enjoy audiobooks as well, so much so that even university libraries in the US have started acquiring audiobooks due to demand. Furthermore, with the ever-reducing price of portable media devices (e.g. smartphones, tablets, MP3 players), listening to audiobooks has become a cinch because audiobooks nowadays are being sold either in CD format or direct download from the vendor's website.
The Quezon City Public Library was chosen as the setting for this study because it is one of the largest public libraries in Metro Manila. Out of the 76 patrons who were willing to answer the survey given to them, 68 (89.47%) said that the Quezon City Public Library should acquire audiobooks, and 71 (93.42%) said that they were willing to borrow audiobooks from the library. Most of the respondents had positive sentiments towards audiobooks with the words "useful", "easy to use", "convenient" and "good" being most frequently used to describe audiobooks. Additionally, 57 (75%) respondents said they preferred to listen to audiobooks using their own portable media players, and 45 (59.21%) respondents said they preferred to download audiobooks straight from a website.
Interviews with the library staff of the Quezon City Public Library also produced promising results. The staff members of the Management Information System were open to the idea of lending audiobooks to patrons in any way that is convenient for both them and the patrons. The staff members of the Technical Services have a system of cataloguing ready if the audiobook collection grows. The librarian from Local History was confident that audiobooks will gain traction from the younger generation.
The promising results of the study have helped create a comprehensive guide for the selection and circulation of audiobooks. Hopefully, more studies in the future about audiobooks will augment the findings of this study.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Collection development (Libraries) -- Philippines -- Quezon City -- Policy statements; Quezon City Public Libraries; Audiobooks -- Philippines -- Quezon City